pH Dependent Photo transformation of Some Pyrimidine: Part II - Singh Chawada, Shivraj; Jain, Shubha (Asian Journal of Chemistry, 2010)
When some pyrimidines, viz., thymine, uracil and cytosine were irradiated by UV light in alkaline medium, they underwent photo transformation giving various products which have been characterized by spectral data and elemental analysis. Theymine undergoes ring expansion by the insertion of —CH3 group whereas uracil and cytosine gives photodimers.